Cardiovascular safety and efficacy of the combined symptomatic slow-acting drug glucosamine and chondroitin sulfate in patients with gonarthrosis - A. P. Rebrov; I. A. Romanova; I. Z. Gaydukova (Современная ревматология)
Objective: to investigate the clinical efficacy and cardiovascular safety of the combined symptomatic slow-acting drug glucosamine and chondroitin sulfate in patients with osteoarthritis (OA) and hypertension.Subjects and methods. The investigation enrolled 44 patients (a female:male ratio of 40:4) aged 54.5±7.4 years with knee OA (duration, 6.4±1.54 years). The patients were blindly randomized into two groups: 1) those who received antihypertensive therapy, teraflex (chondroitin sulfate 400 mg and glucosamine sulfate 500 mg) with/without acetaminophen; 2) those who had antihypertensive therapy and acetaminophen. At baseline and 3 and 6 months after treatment, the investigators assessed a change in the degree of OA by the WOMAC and Lequesne indices, the treatment efficiency evaluated by a physician and a patient using a visual analogue scale, and cardiovascular safety (during the first and last visits) through examination of the antithrombogenic properties of the vascular wall and arterial stiffness.Results. All the patients taking teraflex for 6 months were observed to have a positive effect manifesting as a substantial reduction in WOMAC and Lequesne indices, pain syndrome, and needs for analgesics compared to both the baseline level and parameters in the patients receiving acetaminophen only. Teraflex therapy showed an increase in the fibrinolytic activity of the vascular wall. A more obvious fall in augmentation index and pulse wave velocity was seen in OA and AG patients receiving antihypertensive therapy and teraflex.Conclusion. Group 1 displayed not only reductions in pain syndrome and needs for analgesics, but also no blood pressure destabilization. They also had lower endothelial dysfunction manifesting as enhanced fibrinolytic activity of the vascular wall, decreased brachial and aortic augmentation indices, and lower pulse wave velocity.